2011
DOI: 10.1007/s10865-011-9367-z
|View full text |Cite
|
Sign up to set email alerts
|

Beyond conventional socioeconomic status: examining subjective and objective social status with self-reported health among Asian immigrants

Abstract: Despite mounting evidence for a strong and persistent association between socioeconomic status (SES) and health, this relationship is largely unknown among Asian immigrants, a fast growing minority group in the US population. Previous research has typically focused on objective SES (primarily education and income) and ignored self-perceived SES. Using data from the National Latino and Asian American Study (NLAAS) (N = 1,570), we examined the impact of subjective as well as objective SES upon multiple self-repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 47 publications
6
50
1
Order By: Relevance
“…As in previous research, it was shown that subjective social status assessment provided information about health that could not be captured by socioeconomic status (16)(17)19) . In this study, as in the studies cited, it became clear that, regardless of their social or material circumstances, the way in which women considered their social position was a significant predictor of their perceived health status.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…As in previous research, it was shown that subjective social status assessment provided information about health that could not be captured by socioeconomic status (16)(17)19) . In this study, as in the studies cited, it became clear that, regardless of their social or material circumstances, the way in which women considered their social position was a significant predictor of their perceived health status.…”
Section: Discussionsupporting
confidence: 50%
“…Other authors found similar results to those in this study (18) , indicating that the indicators of socioeconomic status were irrelevant for studying immigrant groups because they did not capture the actual socio-economic situation of these groups, introducing limitations to the study of health inequalities. results between socioeconomic status and subjective social status (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) . The authors argued that subjective social status was based on indicators of socioeconomic status, but that this relationship was weaker in people from ethnic minorities.…”
Section: Discussionmentioning
confidence: 99%
“…These categories were collapsed into a dichotomized outcome for physical and mental health separately, with one indicating ''poor'' or ''fair'' health and zero otherwise (''good'' to ''excellent'') [12,13,[43][44][45].…”
Section: Health Measuresmentioning
confidence: 99%
“…years. Occupation was assessed by participants' selfreported work status and job titles and categorized as: managerial occupations, occupations related to sales, clerical, service sectors, physical labor workers, other occupations such as armed forces, and non-employed [13].…”
Section: Socioeconomic Statusmentioning
confidence: 99%
See 1 more Smart Citation